Something spectacular - Hall, Alexis J. (Hall, Alexis J. Something fabulous (Series), 2023)
"Reluctantly agreeing to help her former flame, Arabella Tarleton woo the famous and flamboyant opera singer Orfeo, Peggy Delancey unexpectedly finds common ground with this celebrated soprano--and an instant connection as they walk the line between friendship, flirtation and something more"--